Service role and outcome as moderators in intercultural service encounters - Sharma, Piyush; Tam, J.L.; Kim, N. (Emerald Group Publishing, 2015)
Purpose – The purpose of this paper is to introduce a comprehensive framework incorporating service roles (customer vs employee) and outcomes (failure vs success) as moderators in the process by which perceived cultural distance (PCD) affects customers and employees in intercultural service encounters (ICSEs). Design/methodology/approach – The authors used a 2×2×3 between-subjects experimental design with Chinese undergraduate students, manipulating service role (customer and employee), outcome (failure and success) and PCD (low, medium and high). Findings – Compared to service employees, customers perceive higher cultural distance and lower interaction comfort (IC), service quality and satisfaction; and stronger negative moderating effect of PCD in ICSEs. Compared to service success, failure results in lower IC; perceived service quality and satisfaction, and these effects are stronger for customers (vs employees). Research limitations/implications – The authors used shorter versions of all the scales to minimize participant fatigue and to increase their involvement along with an experimental design with imaginary service scenario, both of which may restrict the generalizability of the findings. Practical implications – Service managers should focus on customer education and employee training to reduce the negative impact of PCD and prevent service failure rather than try to improve service quality and satisfaction beyond customers’ expectations. Originality/value – The authors extend prior research by exploring the moderating effects of service role (customer vs employee) and outcome (success vs failure) on the direct and indirect effects of PCD on IC, service quality and satisfaction.